Clinical characteristics indicating adenomyosis at the time of hysterectomy: a retrospective study in 291 patients - Ţăran, Florin-Andrei; Wallwiener, Markus; Krämer, Bernhard (Archives of gynecology and obstetrics, 2012)
PurposeTo better characterize adenomyosis as a disease entity.MethodsWe retrospectively reviewed the medical records of women undergoing hysterectomy with a histologic diagnosis of adenomyosis, adenomyosis and leiomyomas, and leiomyomas alone.ResultsThe study included 291 women: 38 with adenomyosis alone, 56 with adenomyosis and leiomyomas, and 197 with leiomyomas alone. In univariate analysis, women with adenomyosis were younger (p = 0.018) and had lower uterine weights (p < 0.001) and more disease-specific symptoms (p = 0.008). In multinomial logistic regression analysis, a lower uterine weight (OR 0.99, CI 95% 0.99-1.0), pelvic pain (OR 4.8, CI 95% 1.5-15.2), a history of smoking (OR 2.6, CI 95% 1.1-6.5) and at least one delivery (OR 4.3, CI 95% 1.5-12.3) were associated with a greater likelihood of having adenomyosis but not leiomyomas alone.ConclusionsWomen undergoing hysterectomy with adenomyosis alone have different clinical characteristics from women with adenomyosis and leiomyomas and from those with only leiomyomas.